Pengaruh Keamanan Siber, Efikasi Diri, Dan Sosialisasi Finansial Digital Terhadap Keberlanjutan UMKM - Thea Amantha Maliagung; Lalu Yayan Ardiansyah; Rina Komala (Income : Digital Business Journal, 2026)
Digital financial literacy has been widely studied as a determinant of micro, small, and medium enterprise (MSME) sustainability, yet most studies remain focused on general financial and digital knowledge dimensions. Other dimensions that shape entrepreneurs' digital financial behavior are rarely examined in depth, namely cybersecurity awareness, digital financial self-efficacy, and digital financial socialization. This study aims to build a conceptual framework on the influence of these three variables on MSME business sustainability. A narrative literature review method was applied to relevant articles published between 2013 and 2026. The review indicates that cybersecurity awareness, digital financial self-efficacy, and digital financial socialization conceptually contribute to business sustainability by strengthening MSME owners' confidence and the security of their digital transactions. The implication is that digital financial literacy programs should not only emphasize product knowledge but also security, self-confidence, and social support in the use of digital financial services.